2005
DOI: 10.5424/sjar/2005031-133
|View full text |Cite
|
Sign up to set email alerts
|

Growth and nitrogen use efficiency of irrigated maize in a semiarid region as affected by nitrogen fertilization

Abstract: The main groundwater pollution factor in irrigated maize production areas is leaching of nitrogen below the root zone. During the years 1999-2001, experiments were carried out on irrigated maize in the semiarid region of CastillaLa Mancha to evaluate the effect of nitrogen in the growth and yield of maize. Three rates of nitrogen were tested: No (0 kg N ha -1 ), Nop (175, 150 and 130 kg N ha -1 in 1999Nop (175, 150 and 130 kg N ha -1 in , 2000Nop (175, 150 and 130 kg N ha -1 in and 2001, and Nc (300 kg N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 16 publications
5
7
0
1
Order By: Relevance
“…These results partially support the findings of Valero et al (2005), who reported that the LAI increased with the application of higher N and decline in LAI appeared in lower N application. In maize, the interval from V12 to V18 stage is critical for N stress since N deficiency could reduce the LAI (Cox et al, 1993).…”
Section: Crop Managementsupporting
confidence: 91%
“…These results partially support the findings of Valero et al (2005), who reported that the LAI increased with the application of higher N and decline in LAI appeared in lower N application. In maize, the interval from V12 to V18 stage is critical for N stress since N deficiency could reduce the LAI (Cox et al, 1993).…”
Section: Crop Managementsupporting
confidence: 91%
“…The N fertilizer application 300 kg ha −1 (F 4 ) resulted in greater LAI than all other treatments. These findings are partially supported with the observation of Valero, Maturano, Ramírez, Martín-Benito, and Alvarez (2005), who concluded that the application of higher N doses linearly increased the LAI.…”
Section: Plant Crop Growth and Yieldsupporting
confidence: 83%
“…After this stage, CGR value declined sharply at 58 -72 DAT, and this was attributed to leaf senescence. The result was similar to earlier reports by [30] and [31]. Increased LAI and total dry matter production using younger seedlings and without standing water have resulted to higher CGR [32].…”
Section: Crop Growth Rate (Cgr) (G•m −2 •D −1 )supporting
confidence: 82%